Comparative analysis of family values in Iranian and Russian cinema - M. I. Kosinova; T. Solgi (Вестник университета)
The purpose of this study is to analyze family values in Iranian and Russian cinema. The main objective of the study is to identify key trends related to the subject of the work based on the analysis of a number of Iranian and Russian films. As a result of the study, the authors found out that in the modern cinema of these countries, we often encounter negative trends indicating the disintegration of the traditional family. The source of these trends is the negative influence of the West, and in particular, Western cinema. The relevance of this topic is determined by the fact that the family as a social institution plays an important role in the society and culture of the country. In turn, cinema as a cultural tool has an impact on the process of forming the institution of the family. In this regard, a certain repertoire policy, regulated at the highest, state level, is able to influence a certain development of the institution of the family of a particular country. The article analyzes the activities of Russia and Iran at the state level aimed at protecting their culture. The main laws and draft laws that contribute (or will contribute) to the strengthening of traditional family values in the culture of Russia and Iran in general and cinema in particular are analyzed.